2010
DOI: 10.1007/s10924-010-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation in an Inert Solid Medium of Poly(Lactic Acid) Polymeric Material by Kibdelosporangium aridum

Abstract: The aim of this work was to estimate the biodegradation of a poly(lactic acid) polymeric material by the actinomycetes Kibdelosporangium aridum using a vermiculite based inert solid medium which could simulate compost medium and enable us to achieve complete carbon balances. The mineralisation rate at the end of the test was compared to those obtained for two basal media. It was shown that cumulative mineralisation after 45 days of degradation was greater (70%) in vermiculite with a basal medium containing gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…CO 2 evolution, weight loss, and molecular weights were measured to evaluate the extent of degradation. The polymer carbon is converted by microorganisms into biomass carbon, carbon dioxide, water soluble by-products and polymer carbon which is not yet degraded (Copinet et al, 2011). Regarding the role of tensile strength to evaluate degradability of polymers (Mostafa et al, 2010 andOrhan et al, 2004) reported that loss in tensile properties is the most relevant practical criterion to characterize degradation of polymer films or fibers that contact with the soil.…”
Section: E Ementioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 evolution, weight loss, and molecular weights were measured to evaluate the extent of degradation. The polymer carbon is converted by microorganisms into biomass carbon, carbon dioxide, water soluble by-products and polymer carbon which is not yet degraded (Copinet et al, 2011). Regarding the role of tensile strength to evaluate degradability of polymers (Mostafa et al, 2010 andOrhan et al, 2004) reported that loss in tensile properties is the most relevant practical criterion to characterize degradation of polymer films or fibers that contact with the soil.…”
Section: E Ementioning
confidence: 99%
“…In most applications that use films or fibers in contact with the soil, loss in tensile properties is the most relevant practical criterion to characterize its degradation (Mostafa et al, 2010 andOrhan et al, 2004). The polymer carbon is converted by microorganisms into biomass carbon, carbon dioxide, water soluble by-products and polymer carbon which is not yet degraded (Copinet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%